Perancangan Tata Letak Proses Produksi Kursi Furnitur Menggunakan Metode Activity Relationship Chart (ARC) di PT. Rama Teknik - Taufik, Taufik; Maulana, Yudi (Universitas Teuku Umar, 2024)
Rama Teknik Company, a manufacturing company in Indonesia founded in 2015, offers innovative business solutions based on research and development. The production process faces layout irregularities which result in disruptions in the production flow. The impact is that the material handling frequency becomes longer and causes material handling costs to become high. Apart from that, the company also experienced failure to achieve production targets. Decision making regarding layout and location is very important in determining a company's long-term operational efficiency. The aim of the research is to redesign the optimal factory layout. To improve the layout of workstations, the research department uses the Activity Relationship Chart (ARC) method which is implemented through FlexSim simulation software. The initial and proposed layouts were simulated using FlexSim software. The stages start from designing the initial layout, then looking for problem gaps. After that, redesign the new layout. The results of the initial layout show 309 finished products, representing a 100% output rate for Queue4 semi-finished goods, 5 warehouses, and 0 finished products in PL. After retesting with the proposed layout, the initial raw materials were 334.49, Queue1 had 285 items, and there was a 38% increase in finished products, a total of 427 seats.